Model of the broadband interferometric optical biosensor in a planar configuration - Blahut, Marek (Photonics Letters of Poland, 2020)
The paper presents numerical studies of the model of an optical sensor based on interference of modes in planar one-dimensional step-index configuration, excited by a broadband light source from a selected spectral range. The refractive index variation of measured external surrounding affects the modal properties of multimode waveguide and the spectral field distribution at the output of the structure. The optical system described is designed to the analysis of biological substances. Full Text: PDF References M. Blahut, "Optical sensor in planar configuration based on multimode interference" Proc. SPIE, 10455, (2017). CrossRef K. Misiakos, et al, "Broad-band Mach-Zehnder interferometers as high performance refractive index sensors: Theory and monolithic implementation", Opt. Express, 22, 8856, (2014). CrossRef K. Gut, "Study of a Broadband Difference Interferometer Based on Low-Cost Polymer Slab Waveguides", Nanomaterials, 9, 729 (2019). CrossRef M. Nordstrom, et al, "Single-Mode Waveguides With SU-8 Polymer Core and Cladding for MOEMS Applications", J. Light. Techn., 25, 1284, (2007). CrossRef D. Segelstein, "The complex refractive index of water", M.S. Thesis, University of Missouri, (1981). DirectLink https://www.yokogawa.com/pl/solutions/products-platforms/ DirectLink